Factors affecting the simple febrile seizures in COVID-19 children: a case–control study from China - Wu, Haohao; Du, Kang; Liang, Xi; Fan, Huijuan; Ba, Ruiqiong; Yang, Junsu; Wang, Yue (Frontiers in Neurology, 2023)
Objective The over-age phenomenon of simple febrile seizures (SFS) was found during the epidemic in COVID-19, but there was no clear explanation, especially in China. This study aimed to analyze the clinical and auxiliary examination features of SFS in children infected with the coronavirus disease 2019 (COVID-19). Methods In total, 78 patients with SFS in the Department of Pediatric and Neurology of Qujing First People's Hospital were enrolled and divided into the COVID-19-positive group (case group) and the COVID-19-negative group (control group). The clinical characteristics, auxiliary examinations, and risk factors were analyzed. Results There were significant differences in age stratification between the two groups. The proportion of children aged over 5 years old in the case group (47.4%) was higher than that of the control group (5%) (p < 0.0001). In terms of sex distribution, the proportion of males in the case group was higher than that in the control group (71.1% vs. 50%), but the difference was not statistically significant (p = 0.0678). For blood cell analysis, the values of white blood cells (WBC), lymphocytes (LY), and monocytes (MN) in the case group were significantly lower than those in the control group (p < 0.01). Serum electrolyte analysis showed the greatest difference in blood sodium. The proportion of hyponatremia in the case group was higher than that in the control group (36.8% vs. 17.5%), but the difference did not reach statistical significance (p = 0.0745). A multivariate logistic regression analysis showed that the history of FS was a independent protective factors for SFS in children with COVID-19 (OR = 0.115, p = 0.009), and age was an independent risk factor for SFS in children with COVID-19 (OR = 1.042, p = 0.001). Conclusion Age distribution, sex a previous history of FS and hyponatremia were different between children with and without COVID-19 in SFS. The history of FS was an independent protective factors for SFS in children with COVID-19.